Developing specialised youth soccer coaching qualifications: An exploratory study of course content and delivery mechanisms - Adams, D.; Cropley, B.; Mullen, R. (International Sport Coaching Journal, 2016)
The purpose of the current study was to empirically examine the potential course content, structure, and delivery mechanisms for a dedicated elite youth coach education programme in football (soccer) in the UK. By achieving this aim it was the intention of the authors to use the findings of this study for the future development of a customised coach education programme. Fifteen elite coaches, working in youth football at the time of the study, participated in one of three focus groups. Emerging from content analysis procedures, the findings placed specific importance on the development of an athlete-centred coaching philosophy, a focus on behaviours and activities associated with positive youth development, a movement away from traditional practices, and the development of the skills required to learn through reflective practice. In addition, a range of pedagogical approaches, including social approaches to learning, mentoring, and blended learning, were highlighted as ways to better deliver education programmes.